Indocyanine Green to Assess Vascularity of Ileal Conduit Anastomosis During Pelvic Exenteration for Recurrent/Persistent Gynecological Cancer: A Pilot Study - Bizzarri, Nicolò; Foschi, Nazario; Loverro, Matteo; Tortorella, Lucia; Santullo, Francesco; Rosati, Andrea; Gueli Alletti, Salvatore; Costantini, Barbara; Gallotta, Valerio; Ferrandina, Gabriella; Fagotti, Anna; Fanfani, Francesco; et al. (Frontiers in Oncology, 2021)
Introduction Pelvic exenteration performed for recurrent/persistent gynecological malignancies has been associated with urological short- and long-term morbidity due to altered vascularization of tissues for previous radiotherapy. The aims of the present study were to describe the use of intravenous indocyanine green (ICG) to assess vascularity of urinary diversion (UD) after pelvic exenteration for gynecologic cancers, to evaluate the feasibility and safety of this technique, and to assess the postoperative complications. Methods Prospective, observational, single-center, pilot study including consecutive patients undergoing anterior or total pelvic exenteration due to persistent/recurrent gynecologic cancers between August 2020 and March 2021 at Fondazione Policlinico Gemelli IRCCS, Rome, Italy. All patients underwent intravenous injection of 3–6 ml of ICG (1.25 mg/ml) once the UD was completed. A near-infrared camera was used to evaluate ICG perfusion of anastomoses (ileum–ileum, right and left ureter with small bowel, and colostomy or colorectal sides of anastomosis) a few seconds after ICG injection. Results Fifteen patients were included in the study. No patient reported adverse reactions to ICG injection. Only 3/15 patients (20.0%) had an optimal ICG perfusion in all anastomoses. The remaining 12 (80.0%) patients had at least one ICG deficit; the most common ICG deficit was on the left ureter: 3 (20.0%) vs. 1 (6.7%) patient had no ICG perfusion on the left vs. right ureter, respectively (p = 0.598). 8/15 (53.3%) and 6/15 (40.0%) patients experienced grade ≥3 30-day early and late postoperative complications, respectively. Of these, two patients had early and one had late postoperative complications directly related to poor perfusion of anastomosis (UD leak, ileum–ileum leak, and benign ureteric stricture); all these cases had a suboptimal intraoperative ICG perfusion. Conclusion The use of ICG to intraoperatively assess the anastomosis perfusion at time of pelvic exenteration for gynecologic malignancy is a feasible and safe technique. The different vascularization of anastomotic stumps may be related to anatomical sites and to previous radiation treatment. This approach could be in support of selecting patients at higher risk of complications who may need personalized follow-up.